Chemical Composition of the Cinnamomum malabatrum Leaf Essential Oil and Analysis of Its Antioxidant, Enzyme Inhibitory and Antibacterial Activities - Aswathi Moothakoottil Kuttithodi; Arunaksharan Narayanankutty; Naduvilthara U. Visakh; Joice Tom Job; Berin Pathrose; Opeyemi Joshua Olatunji; Ahmed Alfarhan; Varsha Ramesh (MDPI AG, 2023)
Cinnamomum species are a group of plants belonging to the Lauraceae family. These plants are predominantly used as spices in various food preparations and other culinary purposes. Furthermore, these plants are attributed to having cosmetic and pharmacological potential. Cinnamomum malabatrum (Burm. f.) J. Presl is an underexplored plant in the Cinnamomum genus. The present study evaluated the chemical composition by a GC-MS analysis and antioxidant properties of the essential oil from C. malabatrum (CMEO). Further, the pharmacological effects were determined as radical quenching, enzyme inhibition and antibacterial activity. The results of the GC-MS analysis indicated the presence of 38.26 % of linalool and 12.43% of caryophyllene in the essential oil. Furthermore, the benzyl benzoate (9.60%), eugenol (8.75%), cinnamaldehyde (7.01%) and humulene (5.32%) were also present in the essential oil. The antioxidant activity was indicated by radical quenching properties, ferric-reducing potential and lipid peroxidation inhibition ex vivo. Further, the enzyme-inhibitory potential was confirmed against the enzymes involved in diabetes and diabetic complications. The results also indicated the antibacterial activity of these essential oils against different Gram-positive and Gram-negative bacteria. The disc diffusion method and minimum inhibitory concentration analysis revealed a higher antibacterial potential for C. malabatrum essential oil. Overall, the results identified the predominant chemical compounds of C. malabatrum essential oil and its biological and pharmacological effects.